Nutritional status of a group of polish children with FASD: A retrospective study - Domin, Agnieszka; Mazur, Artur (Frontiers in Nutrition, 2023)
Introduction: Fetal alcohol spectrum disorders (FASDs) are a leading preventable cause of developmental and psychosocial disorders. Prenatal alcohol exposure can be a cause of growth impairment and metabolic problems. In this study, we analysed data on the growth, weight, and nutritional status of children with FASD. Methods: Patients were recruited from the Department of Pediatrics, Paediatric Endocrinology and Diabetology, and the Outpatient Endocrinology Clinic in Rzeszów, Poland. Each person referred for evaluation had a diagnosis of FASD based on the recommendations of Polish experts. The population consisted of 59 subjects with measurements of weight and height, and the IGF-1 level test was performed. Results: Children with FAS had consistently lower height and weight measurements than children with ND-PAE. In the FAS group, children (<3 percentile) accounted for 42.31 %, and in the ND-PAE group – 18.18 %. The analysis of the whole group showed the highest prevalence of low body weight (below the third percentile) among subjects with FAS - 53.85 %. The prevalence of low body weight and short stature (both parameters < 3rd centile) was found to be 27.11 % in the whole group. Lower mean BMI values were related to the FAS group (21.71 kg/m2) compared to the ND-PAE group (39.62 kg/m2). In the study group, BMI below the fifth percentile was found in 28.81 % of the children, normal weight (5th-85th percentile) in 67.80 %. Discussion: During the care of children with FASD, a continuous evaluation of nutritional status, height, and weight is necessary. This group of patients is often affected by low birth weight, short stature and weight deficiency, which require differential diagnosis and appropriate dietary and therapeutic management.